Comparative Analysis Of Laravel, Lumen, Guzzle, Leaf, and Slim Framework Performance On Rest API Using One Way Anova - Moch. Faisal; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
The rapid advancement of technology has increased the importance of selecting the right framework for RESTful API development. This study compares the performance of five popular PHP frameworks—Laravel, Lumen, Guzzle, Leaf, and Slim—in terms of response time, CPU usage, memory usage, throughput, and error rate. Using Apache JMeter as the testing tool, load testing was conducted across various endpoints with simulated virtual users (up to 75 users). The methodology involved designing a RESTful API with a PostgreSQL database, implementing it using the five frameworks, and performing load tests to measure the defined performance parameters. Statistical analysis using One-Way ANOVA was conducted to determine significant performance differences among the frameworks. The results indicate that each framework has distinct strengths and weaknesses under specific conditions. Frameworks like Lumen and Guzzle demonstrated superior performance in terms of response time and CPU usage, while Slim performed better with higher throughput under certain scenarios. These findings provide critical insights for developers and decision-makers in selecting the most efficient framework based on project requirements. Keyword: RESTful API, PHP frameworks, performance analysis, load testing, Apache JMeter, One-Way ANOVA.